The installation of a common rail diesel engine on a light helicopter of the eurocopter EC120 class (2016)
A feasibility study for the installation of a CRDID (Common Rail Direct Injection Diesel) on a light helicopter is introduced. The total mass available for the CRDID is evaluated starting from fuel consumption and helicopter data. The conversion of an automotive unit was discarded to excessive mass and excessive costs of the conversion. A derivative of an automotive engine was then considered. This solution proved to be feasible. The installation of the new CRDID was then studied. The turbocharger and the cooling system were defined for the application. The result was the evaluation of the power plant installation mass that proved to be much lower than the maximum admissible. The installation is then possible.